Crisis impact on the Romanian economy compared to European Union countries - ZORZOLIU, Raluca (Annals of Spiru Haret University. Economic Series, 2009)
The second half of 2008 marked, in Romania, the entry into technical recession, and during the following periods of time the economic contractions led to a widespread crisis in almost all sectors. In the first half of 2010, Europe recorded the first increase, more or less timid, meaning leaving the recession, but in Romania we continue to record an economic contraction – in other words, the fourth quarter of crisis. Business analysts and business people consider that this setback was caused by the lowering of the population’s purchasing power and government measures taken or just announced, in the first half of 2010, as well as the bankers’ reluctance to lend to firms.